2021
DOI: 10.21831/reid.v7i1.30521
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of learning process: Knowledge of ICT integration among pre-service English language teachers

Abstract: This research aims at investigating the knowledge of ICT integration among the students of English Language Education Study Program at a particular university in Yogyakarta. By employing the quantitative method, this ex-post facto research involved 70 English Department students who had taken microteaching as respondents in a survey to gather the data using a questionnaire. The questionnaire was taken from the model developed by one of the researchers based on the TPACK framework. There are five domains in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…On the contrary, Ciptaningrum et al (2021) revealed that the pre-service English language teachers at a university in Yogyakarta, Indonesia had good skills in technology-related domains but fair skills in the interplay of TPACK. The findings by Ciptaningrum et al (2021) are consistent with those of Bilici et al (2016) and Koehler et al (2014) that teachers need to possess technology, TPACK to effectively integrate technology in their classrooms. Some literature shows that though pre-service teacher trainees acquire some technology skills in teacher education, many of them face challenges in planning technology-driven lessons and teaching with technology during school practice (Kisalama & Kafyulilo, 2012;Mandera, 2018;Ramazanova et al, 2021;Jita, 2018;Wetzel et al, 2014).…”
Section: Pre-service Teacher Trainees' Competencies To Integrate Inst...mentioning
confidence: 93%
See 1 more Smart Citation
“…On the contrary, Ciptaningrum et al (2021) revealed that the pre-service English language teachers at a university in Yogyakarta, Indonesia had good skills in technology-related domains but fair skills in the interplay of TPACK. The findings by Ciptaningrum et al (2021) are consistent with those of Bilici et al (2016) and Koehler et al (2014) that teachers need to possess technology, TPACK to effectively integrate technology in their classrooms. Some literature shows that though pre-service teacher trainees acquire some technology skills in teacher education, many of them face challenges in planning technology-driven lessons and teaching with technology during school practice (Kisalama & Kafyulilo, 2012;Mandera, 2018;Ramazanova et al, 2021;Jita, 2018;Wetzel et al, 2014).…”
Section: Pre-service Teacher Trainees' Competencies To Integrate Inst...mentioning
confidence: 93%
“…Other studies have revealed that although the teaching of educational technology majorly focuses on developing pre-service teacher trainees' technology skills, the majority of them have lower mean scores in the knowledge domains related to technology, which limits their teaching using technology (Kisalama & Kafyulilo, 2012;Pozas & Letzel, 2021;Jita, 2017). On the contrary, Ciptaningrum et al (2021) revealed that the pre-service English language teachers at a university in Yogyakarta, Indonesia had good skills in technology-related domains but fair skills in the interplay of TPACK. The findings by Ciptaningrum et al (2021) are consistent with those of Bilici et al (2016) and Koehler et al (2014) that teachers need to possess technology, TPACK to effectively integrate technology in their classrooms.…”
Section: Pre-service Teacher Trainees' Competencies To Integrate Inst...mentioning
confidence: 99%